Approach to nonisothermal crystallization kinetics of poly(4‐methyl‐1‐pentene) melt: Effect of gamma‐ray. (20th January 2021) - Chang, Yuan‐Hsiang; Zhang, Yulin; Chiang, Donyau; Yang, Fuqian; Lee, Sanboh
Abstract: Understanding the effect of gamma‐ray irradiation on the nonisothermal crystallization of polymer during cooling is of practical importance for the applications and manufacturing of crystallized polymer. In this work, we expose poly(4‐methyl‐1‐pentene) (PMP) to gamma‐ray with different irradiation doses and study the crystallization of the gamma‐ray irradiated PMPs. All the PMPs exhibit a doublet peak in the differential scanning calorimeter thermograms for the cooling rates in a range of 2.5–20°C/min. We use linear superposition of two inverse Gaussian functions to decompose the doublet peak into two individual peaks and analyze the crystallization kinetics of the crystallization processes associated with individual peaks. The Avrami exponent decreases with the decrease of the crystallization temperature and is in a range of 0.96–2.43 for the crystallization near the melting point and a range of 0.72–1.68 for the crystallization away the melting temperature. The activation energy for the crystallization near the melting temperature decreases with the increase of the irradiation dose. For the crystallization away from the melting temperature, the activation energy for the PMPs without gamma‐ray irradiation is smallest. Abstract :